2005
DOI: 10.1258/0956462053420257
|View full text |Cite
|
Sign up to set email alerts
|

HIV and syphilis in young Chinese adults: implications for spread

Abstract: Our objective was to explore the epidemiology of HIV and syphilis at population level in young Chinese adults. The study was carried out in six areas of three Chinese provinces: Zhejiang, Yunnan and Shaanxi. All couples attending the compulsory premarital examination were recruited. Routinely taken blood was collected onto filter paper. Tests for HIV and syphilis used modified particle agglutination techniques. In all, 17,226 individuals were tested. There were no HIV infections in Zhejiang or Shaanxi. In Yunn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…Our report provides a comprehensive view of the reemergence of syphilis in China. These fi ndings are consistent with reports of the exceptional prevalence of syphilis in high-risk groups in China [16][17][18] and of the spread of other STD in China, 19 including a nationwide cross-sectional survey that showed a high prevalence of chlamydial infection, especially in urban coastal areas. 20 Worldwide, resurgence of syphilis in China corresponds to epidemics reported in several cities in the UK, 21 Ireland, 22 the Russian Federation states, 23 and the USA.…”
Section: Discussionsupporting
confidence: 91%
“…Our report provides a comprehensive view of the reemergence of syphilis in China. These fi ndings are consistent with reports of the exceptional prevalence of syphilis in high-risk groups in China [16][17][18] and of the spread of other STD in China, 19 including a nationwide cross-sectional survey that showed a high prevalence of chlamydial infection, especially in urban coastal areas. 20 Worldwide, resurgence of syphilis in China corresponds to epidemics reported in several cities in the UK, 21 Ireland, 22 the Russian Federation states, 23 and the USA.…”
Section: Discussionsupporting
confidence: 91%
“…In their large study of premarital couples, Hesketh et al 173 found similar syphilis prevalence in rural and urban areas in 3 provinces: Yunnan (home of the largest number of injecting drug users in China), Zhejiang (the province with the highest STD incidence), and Shaanxi (a poor central province with low STD and HIV prevalence). Although this suggests widespread unsafe sexual practices, HIV does not yet appear to have spread significantly beyond localized epidemics through heterosexual transmission.…”
Section: Discussionmentioning
confidence: 96%
“…In Yunnan, they did report HIV cases among known high-risk injecting drug users, but unexpectedly, also among low-risk, nondrug users. 173 These results hint that in some places, HIV prevalence may have reached a threshold from Particularly concerning is the increasing prevalence of syphilis among high-risk potential bridge populations. Among drug users, females were infected at 2 to 10 times the rate as their male counterparts.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The prevalence of HIV in China is currently estimated to be 0.06%, corresponding to 11.8 times lower odds of HIV infection than clients in this review [11]. A large study of couples receiving compulsory premarital examinations found a low prevalence of syphilis across various study sites in China (0.33% to 0.71%) [72]. In comparison, clients in this review were found to have 5.7 times higher odds of being infected with syphilis.…”
Section: Discussionmentioning
confidence: 97%